HUBUNGAN PERHATIAN ORANG TUA DENGAN TANGGUNG JAWAB IBADAH REMAJA - Muhammad Syahrul Hasibuan; Ahmad Darlis (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
Education is the main means in efforts to improve the quality of human resources. Without education, it will be difficult to obtain good-quality human resources. The family environment is the first educational environment. The main task of the family is raising children by laying the foundation for moral education and a religious attitude toward life. The nature and personality of children are mainly inherited from parents and other families. This study aims to determine the relationship between parental attention and the responsibility of adolescent worship in the village of Bandar Khalipah, Percut Sei Tuan District. This type of research is quantitative and belongs to the data interval. This study consists of two variables, namely; parental attention (X) is the independent variable and youth worship (Y) is the dependent variable. The population of this study was teenagers in Bandar Khalipah Village, Percut Sei Tuan District, totaling 20 people with stratified sampling, namely representing a population of only 3 teenagers. The results showed that parental attention was in the high category with the aspect of taking care of material needs in the high category and the aspect of creating affection was in the high category and most of the youth's worship was in the good category with the thought aspects of worship being in the bad category, aspects of moral behavior are in the good category, but in this aspect there are still students who are in the bad category.